Influence of subclinical hypothyroidism on indicators of 24-hour arterial blood pressure monitoring in hypertensive patients with high additional risk - Syvolap, V. V.; Novikov, Ye. V.; Potapenko, M. S. (Zaporozhye Medical Journal, 2019)
Significant prevalence of arterial hypertension (40 % of the adult population) and unsatisfactory level of high blood pressure adequate control (only 14 % of the urban and 8 % of the rural population in Ukraine) underlines the need to study the factors influencing AH course and contributing to a lack of antihypertensive therapy efficacy. One of such factors is subclinical hypothyroidism (SH). Aim. To study Influence of subclinical hypothyroidism on indicators of 24-hour arterial blood pressure monitoring in hypertensive patients with high additional risk. Materials and methods. After signing of written informed consent for the study, 124 patients with arterial hypertension (AH) and 16 practically healthy people (control group) were involved. The main group included 32 AH patients (women 87.5 % (n = 28), men 12.5 % (n = 4)) with moderately elevated thyroid stimulating hormone level (TSH) (4.0–15.6 μD/ml) and normal levels of thyroid hormones. The comparison group consisted of 92 AH patients (women 81.52 % (n = 75), men 18.48 % (n = 17)) with normal levels of TSH (0.4–4.0 μD/ml). The groups of patients were matched for age (54.16 ± 10.16) years versus (57.69 ± 9.76) years, (P = 0.093), sex (P = 0.4319), height (P = 0.993), weight (P = 0.719), body surface area (P = 0.901), body mass index (P = 0.669). All patients underwent a combined 24-hour blood pressure monitoring and ECG using a “Cardiology-04-AD-3” device (St. Petersburg, RF). Results. AH patients with or without concomitant SH were of comparable mean daytime and nighttime indices of SBP and DPB, indicators of SBP and DBP variability, PBP, indices for hypertension and hypotension, circadian indices, indices of percentage SBP and DBP increases, SBP and DBP load (with the exception of daytime SBP load). Patients with AH and SH, in contrast to AH patients without SH, tended to have 8.5 % (P < 0.05) higher indices of daytime SBP load, and 19.3 % (P < 0.05) lower daytime DBP hypotension index. Conclusions. AH patients with or without concomitant SH are comparable by the vast majority of ABPM indicators. However, in AH patients with concomitant SH, unlike those without SH, a larger daytime SBP load and a lower daytime DBP hypotension index were detected.